Soybean weed control with preemergent herbicides under "cerrado" - Souza, Itamar Ferreira de (2014)
The effects of cyanazine 2-{[4-chloro-6-(ethylamino)-s-triazin-2-yl] amino} -2-methylpropionitrile), metolachlor (2-chloro-N-(2-ethyl-6-methylphenyl)-N-(2-methoxy-l-methylethyl) acetamide), metribuzin (4-amino-6-tert-buthyl-3-methylthio-astriazin-5 (4H) one) and cinmethylin (7-oxabicicle (2, 2, 1) heptane, 1-methyl-4-(1-methylethyl)-2-(2-methyl-phenylmethoxy)-exo) on soybean (Glycine max (L.) Merr.) weed control were evaluated. Cyanazine applied, either alone or in mixture with cinmethylin was injurious to the crop by a concentration-dependent phytotoxicity. The inicial stand was reduced by cyanazine at 0,75 kg/ha + cinmethylin at 0,42 kg/ha and cyanazine at 1,00 kg/ha + cinmethylin at 0,42 kg/ha. The lowest final stands were observed with cyanazine at 1.00 kg/ha + cinmethylin at 0,42 kg/ha. Cyanazine + metolachlor reduced the phytotoxic effect caused by cyanazine. Eleusine indica and Richardia Brasiliensis were well controlled by all herbicides up to 30 days after application. From that date on, the higher rates of cyanazine were applied, the less control of those weeds were obtained. Alternanthera ficoidea was well controlled by cyanazine, cinmethylin, and metolachlor up to 30 days after application. Ageratum conyzoides was controlled by herbicides tested up to 30 d.a.a. Commelina sp was controled by cyanazine + cinmethylin, cyanazine + metolachlor, and by metolachlor up to 30 d.a.a.